Strengthening and skills development through the implementation of a real marketing campaign: the FormulaUEM - Verónica Baena Graciá; Vicente Padilla Valencia (Universitat Politècnica de València, 2012)
This article describes an innovative cooperative teaching activity developed in a Spanish university that allowed students to get into contact with the professional world while developing some basic skills required in the workplace. Specifically, this paper describes an activity carried out during the 2010/2011 academic year in which senior students of a double degree in Business Administration + Market Research and Techniques, designed and put into practice a real marketing campaign. The activity was also attended by students from the Engineering School of this university. For maximum visibility and gaining the support of companies willing to sponsor the project, marketing and engineering students worked in different teams to design and develop a website, brochures, campaigns on social networks (Facebook, twitter, tuenti, etc.), and develop some mass events, such as sweepstakes or organizing a concert. Some of them got great coverage in the mass media, such as television (MarcaTV), digital media, and forums. To test whether the activity's goals were achieved, two questionnaires were answered among the students (before and after their participation). The excellent results obtained from the descriptive statistics and the t-student means test confirmed the suitability of the proposed activity at the University. Specifically, it is shown that this activity does not only serves to bring students to the professional world, but also enables to develop several core skills required in the workplace such as team working, information integration, critical thinking, responsibility, planning, innovation and communication skills, initiative, and conflict management.